Integration of Cultural and Historical Heritage Ontologies into an Ontological Network - Madanska, Sebiha; Stoyanova-Doycheva, Asya (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2025)
Ontology creation poses integration and interoperability challenges.Ontology integration is a hot topic in artificial intelligence. The article considers variants for integrating ontologies in Bulgarian cultural and historical heritage, which can be used as an Intelligent Tourist Guide’s knowledge base. Cataloguing standard and ontology integration mechanisms using Protégé are discussed.
Keywords: Ontology Integration; Protégé; Ontological Network; Cultural and Historical Heritage; Tourism Domain of Interest